IMPLEMENTATION OF THE DA'WAH OF THE FAJAR EDUCATION FOUNDATION IN INSTILLING ISLAMIC VALUES IN THE COMMUNITY OF DOLOK MASIHUL SUB-DISTRICT, SERDANG BERDAGAI DISTRICT - Nadya Syakilah; Nashrillah (TASAMUH, 2024)
This research aims to know and recognise the da'wah implementation at the Fajar education foundation in instilling Islamic values in residents of Dolok Masihul District, Serdang Bedagai Regency. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews documentation. The results showed that the implementation of the Fajar Education Foundation's da'wah is committed to instilling the value of Islamic values in Dolok Masihul residents through Da'wah Ammah, Da'wah bil Lisan, Da'wah bil Haal, Da'wah bil Hikmah by using the following approaches:  Education and Teaching: through formal and non-formal education about Islamic teachings to the community. Lectures and Discussions: Organizing lectures and discussions on religious topics to increase the understanding of the community. Lectures and discussions on spiritual matters at the Istiqomah ta'lim assembly at the mosque in Dolok Masihul sub-district, commemoration of Islamic holidays, and quarterly meetings in the community. Social and community activities: Engaging in social and community activities to practice the teachings of Islam in daily life. Through the recitation of mothers, fathers, and Mosque Youth or IRMI (Istiqomah Mosque Youth Association). Cultural Approach: cultural approach is one of the approaches that can shape a person's character better. The purpose of the Da'wah is to instil the value of Islamic values for citizens. Through this approach, religious values are born in the community through tawhid, Faith, Faith, worship, tolerance, honesty, and noble character toward fellow human beings. The approach taken by the Fajar Education Foundation is warmly welcomed and a positive response for the community, where it increases understanding and knowledge related to Islam.